2017
DOI: 10.1038/s41598-017-13793-3
|View full text |Cite
|
Sign up to set email alerts
|

Dual Biomembrane Force Probe enables single-cell mechanical analysis of signal crosstalk between multiple molecular species

Abstract: Conventional approaches for studying receptor-mediated cell signaling, such as the western blot and flow cytometry, are limited in three aspects: 1) The perturbing preparation procedures often alter the molecules from their native state on the cell; 2) Long processing time before the final readout makes it difficult to capture transient signaling events (<1 min); 3) The experimental environments are force-free, therefore unable to visualize mechanical signals in real time. In contrast to these methods in bioch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 51 publications
2
48
0
Order By: Relevance
“…5a,b ). Therefore, we combined the compression assay and a newly developed “switch assay” using a dual BFP setup 51 (Fig. 6a lower).…”
Section: Resultsmentioning
confidence: 99%
“…5a,b ). Therefore, we combined the compression assay and a newly developed “switch assay” using a dual BFP setup 51 (Fig. 6a lower).…”
Section: Resultsmentioning
confidence: 99%
“…The off-rate of single TCR-pMHC bond is extracted from the distribution of lifetime using a firstorder irreversible dissociation model [11,155]. A dual BFP has been developed to allow for multiple for temporally distinct ligand presentation to study crosstalk between surface receptors [156]. Finally, deformations of the aspirated cell morphology can be used to monitor pushing and pulling forces, which has been applied to studying T-cell responses to antibodies [157].…”
Section: Methods To Study Force-mediated Receptor-ligand Interactionsmentioning
confidence: 99%
“…25 We also developed a dual biomembrane force probe to visualize integrin biomechanical activation on a living platelet. 26 We found that, upon mechano-signaling of GPIb, αIIbβ3 adopts the EC conformation and possesses affinity and bond lifetime that are intermediate between the well-characterized active and resting states. This inside-out mechano-signaling is distinct from the biochemical signaling by agonists and potentiates the outside-in mechano-signaling of αIIbβ3 for affinity maturation (B).…”
Section: Cellular Controls On Weibel-palade Bodies Affecting Von Willmentioning
confidence: 88%
“…24 Our work highlighted the existence, genesis, and regulation of a semistable intermediate state of αIIbβ3 that is fundamental in mechanically driven thrombosis. 26…”
Section: Cellular Controls On Weibel-palade Bodies Affecting Von Willmentioning
confidence: 99%